Optimizing TESE‐ICSI by laser‐assisted selection of immotile spermatozoa and polarization microscopy for selection of oocytes. (9th October 2012) - Nordhoff, V.; Schüring, A. N.; Krallmann, C.; Zitzmann, M.; Schlatt, S.; Kiesel, L.; Kliesch, S.
Summary : For most azoospermic men testicular sperm extraction (TESE) is the only treatment, however it presents challenges for the ART laboratory, as the retrieval of motile spermatozoa is difficult. In the absence of sperm movement no unequivocal distinction can be made between either dead or immotile, but vital spermatozoa. However, a single laser shot directed to the tip of the tail allows recognition of viability because the flagellum coils at the area of impact. To rank the quality and the maturity of oocytes, polarization microscopy can be used. The zona score and the visualization of the meiotic spindle correlate with implantation and pregnancy rates. We compared 65 TESE‐ICSI cycles of the years 2007 and 2008 (Group 1, G1) with 58 TESE‐ICSI cycles of the years 2009 and 2010 (Group 2, G2). Testicular spermatozoa were injected according to motility and morphology into selected oocytes. In G1 both, oocyte and spermatozoa were rated using light microscopy only, whereas in G2 the laser was used for sperm selection and the oocytes were rated by light and polarization microscopy. In G2 we enhanced our fertilization rate (FR) significantly in comparison to G1 (G1 42.1% vs. G2 52.7%, p  < 0.001). The fertilization rate with immotile, but vital spermatozoa improved significantly when applying laser‐based selection ( p  = 0.006). The laser selection of immotile spermatozoa and the use of polarization microscopy can enhance the FR of TESE‐ICSI. No negative effect of the laser was seen on birth rates. The FR with immotile, but vital spermatozoa clearly benefits from laser selection and is a non‐hazardous and safe method for the selection of viable but immotile sperm. To our knowledge this is the first report using new technology creating novel endpoints for the analysis of spermatozoa and oocytes in TESE‐ICSI.